Morphological and molecular characterization of Termitomyces (Lyophyllaceae, Agaricales) in Thailand - NICHAREE JANNUAL; MINGKWAN NIPITWATTANAPHON; SASITORN HASIN; Tharnrat Kaewgrajang (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Jannual N, Nipitwattanaphon M, Hasin S, Kaewgrajang T. 2020. Morphological and molecular characterization of Termitomyces (Lyophyllaceae, Agaricales) in Thailand. Biodiversitas 21: 2481-2491. Termitomyces is considered to be a highly prized delicacy collected both for home consumption and for sale in local markets. Although the taxonomic information about this genus is well known in Africa, the identification of Termitomyces species in Thailand is unclear. Therefore, this study presented an assessment of phylogenetic relationships in the genus Termitomyces by means of sequencing of the ITS1-5.8S-ITS2 region and the species characterization by combination of morphological data and molecular data. Total of 61 Termitomyces specimens was collected from a variety of geographical localities of Thailand. They were classified into six species, including T. clypeatus, T. cylindricus, T. fuliginosus, T. heimii, T. microcarpus, and T. striatus based on morphological characteristics combining with molecular characteristics. This is the first diagnostic key of Thai Termitomyces.